2019
DOI: 10.1089/wound.2018.0889
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Survival and Accelerated Perfusion of Skin Flap to Recipient Site Following Administration of Human α1-Antitrypsin in Murine Models

Abstract: Objective: Skin flaps are routinely used in reconstructive surgery yet remain susceptible to ischemia and necrosis. Distant flaps require lengthy time to detach causing patient discomfort. Human a1-antitrypsin (hAAT) is a clinically available serum glycoprotein. hAAT was shown to support mature vessel formation and enhance tissue survival following ischemia-reperfusion injuries. The purpose of the presented study was to examine the effect of hAAT on skin flap survival and distant ''tube'' flap perfusion throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…At the same time, however, it should be noted that RT-PCR results in the present study show that the expression of IL-1β in wound explants is diminished by both hAAT formulations, while VEGF expression, a classic inflammatory downstream responder, is elevated. This is consistent with accelerated perfusion of skin flaps in hAAT-rich conditions [9] and upregulation of VEGF in angiogenesis studies that examine clinical-grade hAAT [34].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…At the same time, however, it should be noted that RT-PCR results in the present study show that the expression of IL-1β in wound explants is diminished by both hAAT formulations, while VEGF expression, a classic inflammatory downstream responder, is elevated. This is consistent with accelerated perfusion of skin flaps in hAAT-rich conditions [9] and upregulation of VEGF in angiogenesis studies that examine clinical-grade hAAT [34].…”
Section: Discussionsupporting
confidence: 77%
“…Human alpha1-antitrypsin (hAAT) is an endogenous circulating 52-kDa serine protease inhibitor, whose concentrations rise 4-6 fold during the acute inflammatory process. hAAT is mostly known in the context of hAAT deficiency, a genetic condition associated with early-onset pulmonary emphysema and necrotizing panniculitis, which is treated by weekly infusions of serum-purified hAAT [9,10]. However, evidence from recent decades has pointed to hAAT also being a potent anti-inflammatory, immunomodulatory, antibacterial and tissue-protective agent [11][12][13].…”
Section: Of 12mentioning
confidence: 99%
See 1 more Smart Citation
“…So, skin flap surgery techniques were suggested to reduce the risks of arterial/venous occlusion and ischemia 25 . In addition, many therapeutic agents have been proven to enhance skin flap survival via the prevention of inflammation, providing free-radical scavenging, increasing angiogenesis, and/or enrichment of the microvascular network 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common use of hAAT is in the treatment of genetic hAAT deficiency, a disorder that causes early onset pulmonary emphysema, vasculitis, poor wound healing, and necrotizing panniculitis. 8,9 AAT is also a pro-resolution/inflammation-modulating, immunomodulatory, antibacterial, and tissue-protective molecule. [10][11][12] Animal studies have shown that hAAT therapy has a protective effect in various ischemia-reperfusion models and skin flap training, encouraging tissue restoration and revascularization.…”
Section: Introductionmentioning
confidence: 99%